Comparative analysis of interfacial composition and structure of fat globules in human milk and infant formulas. (March 2022) - Pan, Yue; Liu, Lu; Tian, Songfan; Li, Xiaodong; Hussain, Muhammad; Li, Chunmei; Zhang, Lihong; Zhang, Qiumei; Leng, Youbin; Jiang, Shilong; Liang, Shuyan
Abstract: In this study, we analyzed and compared the fat globule interfacial compositions and structures in human milk and three types of infant formulas (IF1: supplied with MFGM, IF2: without MFGM and soy lecithin, IF3: supplied with soy lecithin). The results suggested that the interfacial protein composition of IF1 was comparatively closer to human milk, but still lacked certain bioactive MFGM proteins including XO, ADPH and PAS6/7. Considering the interfacial phospholipid, we observed 23, 31, and 29 phospholipid species that could be used to distinguish human milk and infant formulas (IF1, IF2 and IF3). We also found that phosphatidylinositol (PI) and phosphatidylserine (PS), which can absorb lipase, phosphatidylethanolamine (PE), and phosphatidylcholine (PC) and connect functional fatty acids, were lacking in infant formulas. Moreover, the infant formulas had a smaller average particle size of 0.38 μm and a thicker interfacial layer that interacted with the casein micelles. Even if IF1 included MFGM, fat globules structures like those found in human milk did not form, and the majority of the MFGM was still in the aqueous phase in free form. Overall, the comprehensive analysis in this study could be used to simulate or mimic human milk lipids at the supramolecular level. Graphical abstract: Image 1 Highlights: Infant formula with MFGM showed closer to the interface composition of human milk. Infant formulas lack interface phospholipids related to the fat globule structure. Infant formulas had a thicker interface layer and interacted with casein micelles. Most MFGM in infant formulas existed in the aqueous phase as a free form. Infant formulas did not form a fat globule structure like human milk.